Archival Leadership? - McIntosh, Robert (Archivaria)

(untitled) (Association of Canadian Archivists, 2024)
Canadian archivists – members of a community that for many decades has thought deeply and widely about their profession – have published little about archival leadership. This neglect of leadership extends in fact throughout Canadian and English-language archival research journals. This short article aims to take a small step toward filling this large and perplexing gap in our scholarship. Two central questions are addressed: What does leadership in an archives look like? and Does this leadership differ at all in key respects from leadership in other institutions? In other words, do archivists have to be managed differently because the culture of an archives is sufficiently distinct from that of other workplaces? Outlining six aspects of leadership, the article addresses the qualities associated with successfully leading a team within an archives or with heading an archives. It then sketches six distinct features of the culture of an archives, arguing that archivists do need to be managed differently; leadership success hinges on sensitivity to the unique qualities of archival culture. This counterpoint closes by expressing hope that it provokes a reaction – that others will step forward to enrich reflection and debate on the distinct (or not) qualities of archival leadership.